Yeasts associated with an abandoned mining area in Pernek and their tolerance to different chemical elements - Vadkertiová, Renáta; Molnárová, Jana; Lux, Alexander; Vaculík, Marek; Lišková, Desana (Folia microbiologica, 2016)
Four plants, Cirsium arvense (creeping thistle), Equisetum arvense (field horsetail), Oxalis acetosella (wood sorrel) and Phragmites australis (common reed), which grew in an abandoned Sb-mining area in Pernek (Malé Karpaty Mts., Slovakia), were investigated for the yeast species. Yeasts were isolated from both the leaves of the plants and the soil adjacent to the plants. In total, 65 yeast cultures, belonging to 11 ascomycetous and 5 basidiomycetous yeast species, were isolated. The species most frequently isolated from both the soil and leaf samples were Trichosporon porosum, Galactomyces candidus and Candida solani, whereas Aureobasidium pullulans, Candida tsuchiyae and Sporidiobolus metaroseus were isolated exclusively from the plant leaves. All the yeast species isolated were tested for their tolerance to two heavy metals (Cd, Zn) and three metalloids (As, Sb and Si). The yeasts isolated from both the leaves and soils exhibited a high tolerance level to both As and Sb, present in elevated concentrations at the locality. Among the yeast species tested, Cryptococcus musci, a close relative to Cryptococcus humicola, was the species most tolerant to all the chemical elements tested, with the exception of Si. It grew in the presence of 200 mmol/L Zn, 200 mmol/L Cd, 60 mmol/L As and 50 mmol/L Sb, and therefore, it can be considered as a multi-tolerant species. Some of the yeast species were tolerant to the individual chemical elements. The yeast-like species Trichosporon laibachii exhibited the highest tolerance to Si of all yeasts tested, and Cryptococcus flavescens and Lindnera saturnus showed the same tolerance as Cryptococcus musci to Zn and As, respectively. The majority of the yeasts showed a notably low tolerance to Cd (not exceeded 0.5 mmol/L), which was present in small amounts in the soil. However, Candida solani, isolated from the soil, exhibited a higher tolerance to Cd (20 mmol/L) than to As (2 mmol/L).
Keywords: nebezpečné látky; rostliny; kvasinky; Plant Leaves; Plants; půda; Environmental Microbiology; Mining; Slovakia; Adaptation, Biological; Yeasts; Slovenská republika; Hazardous Substances; mikrobiologie životního prostředí; hornictví; Environment; životní prostředí; biologická adaptace; listy rostlin; Soil